A matter of style? organizational agency in global public policy - Bayerlein, Louisa 1991-; Knill, Christoph 1965-; Steinebach, Yves 1987- (Cambridge University Press, 2020)
International public administrations (IPAs) have become an essential feature of global governance, contributing to what some have described as the 'bureaucratization of world politics'. While we do know that IPAs matter for international politics, we neither know exactly to what extent nor how exactly they matter for international organizations' policy making processes and subsequent outputs. This book provides an innovative perspective on IPAs and their agency in introducing the concept of administrative styles to the study of international organizations and global public policy. It argues that the administrative bodies of international organizations can develop informal working routines that allow them to exert influence beyond their formal autonomy and mandate. The theoretical argument is tested by an encompassing comparative assessment of administrative styles and their determinants across eight IPAs providing rich empirical insight gathered in more than 100 expert interviews
Keywords: International agencies / Administration; International organization; Political planning; Management